Corporate learning at Merck: strategy, performance goals, and measuring success - Zeller, Theresa (Henry Stewart Talks, 2025)
Merck, Learning vs. training, Skill gap analysis, Upskilling, Measuring success, Performance KPIs, Learning and business strategy